Enhancing Fish Processing Skills through STEAM-Based Smart Technology: A Capacity-Building Model for Small-Scale Tongkol (Euthynnus affinis) Processors in Rural Indonesia - Muhammad Nurtanto; Rouf Muhammad; Hana Nurdina; Hamid Ramadhan Nur; Mulyono Mulyono; Rina Febriana Hendrawan; Farid Mutohhari; Muhammad Fajar; Hanung Difa Safitri; Galas Dimas Aryo Prayudo (Jurnal Medika: Medika, 2026)
Small-scale fish processing in Indonesia’s coastal regions continues to face major challenges, including inconsistent product quality, limited technical skills, and minimal utilization of appropriate processing technologies. These conditions contribute to the low added value and weak competitiveness of micro-scale tuna processing enterprises. This program aims to enhance technical capacity, product quality, and overall productivity of MSMEs through the implementation of Smart Fish Processing technology grounded in STEAM principles and facilitated using a Participatory Action Research (PAR) approach. A total of 25 MSME members participated in awareness sessions, technology diffusion activities, hands-on training, demonstrations, and intensive mentoring over a two-month period. The results indicate a significant improvement in participants’ knowledge of hygiene, sanitation, and modern processing techniques based on pre–post test scores. Technical skill enhancement was reflected in their ability to operate the smart steaming unit, standardize processing parameters, and produce three value-added products: steamed tuna, tuna floss, and tuna broth concentrate. During the program, production capacity increased to a cumulative total of 1,498 kg of steamed fish, 419 kg of tuna floss, and 548 kg of shredded tuna, yielding total sales of IDR 153.44 million and a net profit of IDR 45.9 million. Qualitative findings from interviews and FGDs show increased participant confidence, more structured production collaboration, and emerging digital marketing initiatives through WhatsApp and Facebook. Overall, the integration of controlled processing technology with participatory learning effectively improved product quality, productivity, and business capacity among coastal fish processors. The Smart Fish Processing model demonstrates strong potential for replication among fisheries-based MSMEs in other regions with similar characteristics.